2018
DOI: 10.1002/anie.201810599
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Enantioselective Aldol Reactions of Unprotected Carboxylic Acids under Phosphine Oxide Catalysis

Abstract: The first catalytic enantioselective aldol reaction of various unprotected carboxylic acids is described. In the presence of ac hiral bis(phosphine oxide) as aL ewis base catalyst, carboxylic acids were activated with silicon tetrachloride to form the corresponding bis(trichlorosilyl)enediolates in situ, which subsequently underwent an aldol reaction with an aldehyde or aketone to produce b-hydroxycarboxylic acids in high enantioselectivities of up to 92 %ee. Scheme 1. Enantioselective aldol reactions of carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Recently, the enantioselective addition reaction of diboryl or disilyl enolates (enediolates) has been achieved using only a catalytic amount of a chiral source. [3][4][5] Shimizu and Kanai have reported the catalytic enantioselective Mannich-type reaction of alkyl carboxylic acids with a chiral boron catalyst. [3a] Moreover, Mitsunuma and Kanai have very recently achieved the boroncatalyzed enantioselective aldol reaction to aldehydes (Scheme 1a).…”
mentioning
confidence: 99%
“…Recently, the enantioselective addition reaction of diboryl or disilyl enolates (enediolates) has been achieved using only a catalytic amount of a chiral source. [3][4][5] Shimizu and Kanai have reported the catalytic enantioselective Mannich-type reaction of alkyl carboxylic acids with a chiral boron catalyst. [3a] Moreover, Mitsunuma and Kanai have very recently achieved the boroncatalyzed enantioselective aldol reaction to aldehydes (Scheme 1a).…”
mentioning
confidence: 99%
“…[21] Thec onfigurations of the other products were assigned by analogy or by comparison of the sign of the optical rotation with reported data. X-ray crystallographic analysis of 11 ba disclosed its absolute configuration to be 2R,3R.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Catalytic Chemoselective Activation of Carboxylic Acids promoting a catalytic asymmetric aldol reaction of carboxylic acids, 10 another fundamental and synthetically useful C-C bond-forming reaction. [11][12][13][14] Here we found that in-situ pre-conversion of carboxylic acids to siloxy esters dramatically facilitated the boron-catalyzed, carboxylic acid-selective asymmetric aldol reaction. The siloxy group worked as a traceless activator, allowing for the direct use of carboxyl group-containing multifunctional drugs and natural products themselves as substrates of catalytic asymmetric aldol reactions.…”
Section: Introductionmentioning
confidence: 99%